Ralstonia solanacearum Infection Disturbed the Microbiome Structure Throughout the Whole Tobacco Crop Niche as Well as the Nitrogen Metabolism in Soil - Wang, Zhaobao; Zhang, Yuzhen; Bo, Guodong; Zhang, Yanping; Chen, Yu; Shen, Minchong; Zhang, Peng; Li, Guitong; Zhou, Jie; Li, Zhengfeng; Yang, Jianming (Frontiers in Bioengineering and Biotechnology, 2022)
Infections of Ralstonia solanacearum result in huge agricultural and economic losses. As known, the proposal of effective biological measures for the control of soil disease depends on the complex interactions between pathogens, soil microbiota and soil properties, which remains to be studied. Previous studies have shown that the phosphorus availability increased pathobiome abundance and infection of rhizosphere microbial networks by Ralstonia. Similarly, as a nutrient necessary for plant growth, nitrogen has also been suggested to be strongly associated with Ralstonia infection. To further reveal the relationship between soil nitrogen content, soil nitrogen metabolism and Ralstonia pathogens, we investigated the effects of R. solanacearum infection on the whole tobacco niche and its soil nitrogen metabolism. The results demonstrated that Ralstonia infection resulted in a reduction of the ammonium nitrogen in soil and the total nitrogen in plant. The microbes in rhizosphere and the plant’s endophytes were also significantly disturbed by the infection. Rhodanobacter which is involved in nitrogen metabolism significantly decreased. Moreover, the load of microbial nitrogen metabolism genes in the rhizosphere soil significantly varied after the infection, resulting in a stronger denitrification process in the diseased soil. These results suggest that the application management strategies of nitrogen fertilizing and a balanced regulation of the rhizosphere and the endophytic microbes could be promising strategies in the biological control of soil-borne secondary disasters.